Concerted effect of Ni-in and S-out on ReS2 nanostructures towards high-efficiency oxygen evolution reaction. Issue 22 (28th February 2022) - Das, Tapas K.; Ping, Tapan; Mohapatra, Manoj; Anwar, Shahid; Gopinath, Chinnakonda S.; Jena, Bikash Kumar
Abstract : The excellent OER activity benefiting from the rapid charge transfer caused by the concerted effect of Ni-in and S-out on a ReS2 nanostructure. Abstract : Herein, a one-step hydrothermal reaction is developed to synthesize a Ni-doped ReS2 nanostructure with sulphur defects. The material exhibited excellent OER activity with a current density of 10 mA cm −2 at an overpotential of 270 mV, a low Tafel slope of 31 mV dec −1, and good long-term durability of 10 h in 1 M KOH. It shows high faradaic efficiency of 96%, benefiting from the rapid charge transfer caused by the concerted effect of Ni-in and S-out on the ReS2 nanostructure.